RISIKO INVESTASI SAHAM SECOND LINER DENGAN TAIL VALUE AT RISK - Di Asih I Maruddani; Tutut Dewi Astuti (MIX: JURNAL ILMIAH MANAJEMEN, 2021)
This pandemic which has been going on for almost a year, is very influential in all fields. Economic growth and investment in all countries have been declined dramatically.  Indonesian Composite Stock Price Index (CSPI) as an indicator of stock performance in Indonesia is weakening. Big caps stocks, which are usually the main driver for domestic bourses, fell sharply uncontrollably. However, second liner stocks managed to hold down the CSPI throughout 2020. This condition made many investors switch to stocks in this group. Low prices and high profit potential are attractive considerations. But high price fluctuations make investing riskier. Tail Value at Risk (T-VaR) as a measure of risk in a bad situation is the right measure so that investors can estimate the worst possibility and a larger reserve fund. The purpose of this study is to measure the investment risk in second liner stocks based on T-VaR. The six stocks of Pefindo 25 Index indicate that at a 95% significance level, the investment risk in second liner stocks will be in the range 6,14% - 8,22% of the investment.